The role of laboratory evaluation of umbilical cord blood in diagnosing early onset neonatal sepsis - صبيره عبير; عدنان ديوب (Latakia University Journal -Medical Sciences Series, 2024)
Background: Early onset sepsis(EOS) remains a common disease in neonates admitted to neonatal intensive care unit(NICU) with poor outcome, especially in cases that associated with diagnostic delay. Objective: The aim of this study was to evaluate the role of umbilical cord blood in diagnosis early onset neonatal sepsis. Materials and Methods: An observational descriptive study (cross-sectional) was conducted for the period one year (May 2022–May 2023) at Tishreen University Hospital in Lattakia -Syria. The study included two groups of neonates were compared: group I consisted of 56 neonates with a proven diagnosis of EOS , whereas group II consisted of 66 neonates without EOS. Complete blood count(CBC) and C-reactive protein(CRP) were performed immediately after delivery on umbilical blood cord, and on peripheral blood samples after 24 hours with comparison values between two groups. Results: The results showed that 45.9% of the study population had EOS . There were no significant differences in means of WBC, Neut, Lym, PLT and CRP values on umbilical cord blood analysis between two groups(p>0.05). In addition to , means of WBC ,Neut ,Lym, PLT and CRP values on peripheral blood samples between two groups were significantly different(group I versus group II);(30.57±16.1 versus20.52±19.5,p:0.003),(70.60±13.6 versus 55.46±9.2,p:0.0001), and (9.82±14.3 versus4.07±1.9,p:0.002) respectively without significant difference regarding PLT. Conclusion: Analysis of CBC, CRP in umbilical cord blood samples immediately after delivery can’t help in distinguishing neonates with EOS whereas WBC count, Neut, and CRP on peripheral blood were superior in diagnostic accuracy for EOS.